2022
DOI: 10.1093/jmcb/mjac038
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of stem cells in mammalian esophageal stratified squamous epithelia

Abstract: Somatic stem cells are essential for the maintenance of tissue homeostasis. Despite its importance, how the esophageal stratified squamous epithelium executes its self-renewal and maintenance remains elusive. In this study, using 5-bromo-2'-deoxyuridine (BrdU) label-chase in rats in vivo and rat esophageal organoids in vitro together with genome-wide DNA methylation and single-cell RNA sequencing, we identified a slow-cycling/quiescent stem cell population that contained high levels of hemidesmosomes (HDs) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…3c). However, these p63 + Sox2 + cells were CK14 high cells, indicating that they represented the basal layer cells with stemness property (Col17A1 high ) and growth property (MKi67 high ), which consistent with our previous study [24]. In contrast, the p63 -Sox2 + population were CK13 high CK14 low/negative cells expressing high levels of differentiation-related genes, such as Sprr1a, suggesting that p63 -Sox2 + cells were suprabasal cells.…”
Section: The Landscape Of D3-organoid Formation Development and Matur...supporting
confidence: 90%
See 4 more Smart Citations
“…3c). However, these p63 + Sox2 + cells were CK14 high cells, indicating that they represented the basal layer cells with stemness property (Col17A1 high ) and growth property (MKi67 high ), which consistent with our previous study [24]. In contrast, the p63 -Sox2 + population were CK13 high CK14 low/negative cells expressing high levels of differentiation-related genes, such as Sprr1a, suggesting that p63 -Sox2 + cells were suprabasal cells.…”
Section: The Landscape Of D3-organoid Formation Development and Matur...supporting
confidence: 90%
“…To better understand the dynamics of tissue homeostasis, especially proliferation-differentiation at cellular levels, during formation, development and maturation of D3-organoids, we next performed immunofluorescence analyses using various squamous epithelial cell markers, including the endoderm undifferentiated keratinocyte marker cytokeratin14 (CK14), the endoderm differentiated keratinocyte marker cytokeratin13 (CK13), the stemness pluripotent markers p63 and Sox2, and DNA marker DAPI [24]. Consistent with the results obtained from the daily snapshots of phase-contrast microscopy and H&E-stained organoid cross-section analyses, immunofluorescence results revealed that D3-organoids at Day 2 to Day 3 grew as asymmetric small clumps, in which all cells were stained positively for p63, Sox2 and CK14 but negatively for CK13 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations